Teknologi Portable Inflated Greenhouse Sebagai Fasilitas Pendukung Peningkatan Ketahanan Pangan Dan Pertanian Perkotaan (Urban Farming) - Ronny Durrotun Nasihien; Diah Ayu Restuti Wulandari; Achfas Zacoeb; Harimurti .; M. Ikhsan Setiawan (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
Agricultural Urban (Urban Farming) utilizing land intensification, in order to meet the needs of the fresh fruit and vegetables daily for the public residential/housing in urban areas. Portable Technology Greenhouse inflated as urban agriculture production support facilities, can be built and transferred to a residential location / specific housing is easy, safe, fast and lightweight (PVC 0,55mm Tarpaulin) so that urban agricultural products closer to consumers in urban settlements, the impact price getting cheaper, but quality. The long term goal is to develop protitipe Portable inflated Greenhouse as facilities Urban Farming which fulfills the power, speed, effectiveness, comfort and encourage crops of fruit / vegetable hydroponic hygienic, cheap and profitable, so that the product Portable inflated Greenhouse automatically support an increase in food production of the National, Specific target is the availability protitipe Portable Greenhouse inflated as Urban Farming facility in order to increase productivity of crops of fruit/vegetable hydroponic hygienic, cheap and profitable, so the high prospects for mass production in order to meet national food requirements. Methods using methods Experiments and Action Research, starting with the development of the design, manufacture, testing and repair of prototype Portable inflated Greenhouse includes (1) a test of strength and endurance of materials Portable inflated Greenhouse to weather, (2) test material Portable inflated Greenhouse most effective as a component of the structure, (3) test the speed of manufacture, transport, assembly, installation, dismantling Portable inflated Greenhouse, (4) the test temperature, humidity and air pressure within the Portable inflated Greenhouse, (5) test crops of fruit/vegetables hydroponically are suitable to be developed in inflated portable building a greenhouse in order to obtain yields hygienic, inexpensive andprofitable.The first year developing a prototype design Portable Greenhouse inflated, followed prototyping and ends with prototype testing and field trials at The Lab Narotama, published in the SeminarS/Proceeding International and International Journals indexed, filed a registration PATENT Kemenkumham.The results this research were published in the Appropriate Technology Seminar/Proceeding International and International Journals indexed, processed PATENT Kemenkumham, and is eligible to be mass produced to support the acceleration of National hygienic food production, cheap and profitable